Answer:
see explanation
Explanation:
Given the roots are x= 3, x = 2 + 2i and x = 2 - 2i
Then the factors are
(x - 3), (x - (2 + 2i)) and (x - (2 - 2i))
This is the line where the error has been made as the complex roots have been added to x instead of being subtracted from x
The next line should be
(x - 3)(x - 2 - 2i)(x - 2 + 2i)
= (x - 3)((x - 2)² - 4i² ) → i² = - 1
= (x - 3)(x² - 4x + 4 + 4)
= (x - 3)(x² - 4x + 8)
Multiply each term in the second factor by each term in the first factor
= x³ - 4x² + 8x - 3x² + 12x - 24 ← collect like terms
= x³ - 7x² + 20x - 24